Research of fracturing in the body of ground water dams - Makhmudov Abdulatif; Shakirov Bakhtiyar; Ermatov Qobiljon; Shakirov Boburmirzo; Uljaev Farokhiddin (BIO Web of Conferences)
The basic principle of centrifugal modeling is given. The main similarity relationships when modeling earth dams using a centrifuge: density, relative deformation and stress are the same, which makes it possible to predict the assessm ent of cracking in more detail. Great attention is always paid to the reliability and safety of hydraulic structures. On the other hand, performing scientific research work, it is possible to understand that the reliability of underground water dams, their safety and serviceability are directly dependent on the dam’s resistance to cracking. Scientific studies have confirmed the assumption that the main unevenness of the sediments is related to the manifestation of subsidence deformations of the coastal slope during the filling of the reservoir. Pre-moistening of the foundation makes only a part of the deformations of the settlement, therefore, when filling the reservoir, relatively large settlements of the foundation and their significant unevenness can be expected. The results of our scientific research will be reflected in future studies of the effects of lake sediments on water reservoirs.